The Oxford handbook of talent management - Collings, David G.; Mellahi, Kamel; Cascio, Wayne F. (Oxford : Oxford University Press, 2017)
Draws upon perspectives from, inter alia, human resource management, psychology, and strategy to chart the topography of the area of talent management and to establish the base of knowledge in the field of talen management.
Human Capital Resource Complementarities / Robert E. Ployhart, Ormonde R. Cragun -- Talent or Not: Employee Reactions to Talent Designations / Maria Christina Meyers, Nicky Dries, Giverny De Boeck -- Managing Talent Across Organizations: The Portability of Individual Performance / Gina Dokko, Winnie Jiang -- Star Performers / Ernest O'Boyle, Sydney Kroska -- Talent Management in Small- and Medium-Sized Enterprises / Marion Festing, Katharina Harsch, Lynn Schäfer, Hugh Scullion -- The Potential for Leadership / Walter C. Borman, Rob F. Silzer -- Talent Development: Building Organizational Capability / David V. Day, Patricia M. G. O'Connor -- Talent Management in Multinational Corporations / Ingmar Björkman, Mats Ehrnrooth, Kristiina Mäkelä, Adam Smale, Jennie Sumelius -- Integrating Talent and Diversity Management / Darren Baker, Elisabeth Kelan -- How is Technology Changing Talent Management? / Gavin O'Shea, Kerrin E. George -- Managing Talent Flows Through Internal and External Labour Markets / Matthew Bidwell -- Succession Planning: Talent Management's Forgotten, but Critical Tool / Anthony J. Nyberg, Donald J. Schepker, Ormonde R. Cragun, Patrick M. Wright -- Workforce Differentiation / David G. Collings -- The Historical Context of Talent Management / Peter Cappelli, J.R. Keller -- Virtual Teams: Utilizing Talent Management Thinking to Assess What We Currently Know about Making Virtual Teams Successful / Michael Travis Maynard, Matti Vartiainen, Diana Sanchez -- Talent and Teams / Rebecca R. Kehoe, Blythe L. Rosikiewicz, Daniel Tzabbar -- Straight Talk about Selecting for Upper-Management / Scott Highhouse, Margaret E. Brooks -- HR Metrics and Talent Analytics / Alexis A. Fink, Michael C. Sturman -- Talent Management in Emerging Economies / Fang Lee Cooke -- Within-Person Variability in Performance / Amirali Minbashian -- Introduction / David G. Collings, Kamel Mellahi, Wayn
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 28, 2017).
Keywords: Personnel management